2022
DOI: 10.3389/fmicb.2022.988871
|View full text |Cite
|
Sign up to set email alerts
|

Deep-branching ANME-1c archaea grow at the upper temperature limit of anaerobic oxidation of methane

Abstract: In seafloor sediments, the anaerobic oxidation of methane (AOM) consumes most of the methane formed in anoxic layers, preventing this greenhouse gas from reaching the water column and finally the atmosphere. AOM is performed by syntrophic consortia of specific anaerobic methane-oxidizing archaea (ANME) and sulfate-reducing bacteria (SRB). Cultures with diverse AOM partners exist at temperatures between 12°C and 60°C. Here, from hydrothermally heated sediments of the Guaymas Basin, we cultured deep-branching AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 144 publications
0
13
0
Order By: Relevance
“…The gene of large hydrogenase subunit is a part of the cluster, which codes for uptake hydrogenase small subunit precursor (MCL7474639), four hydrogenase assembly proteins HypDEFC (MCL7474633-36) and hydrogenase maturation protease (MCL7474637). Genes for [FeFe] and [NiFe] hydrogenases were identified in ANME-1 and Methanoperedenaceae [ 23 , 57 , 63 , 64 ], but as far as we know, the presence of hydrogenases in the genomes of ANME-2 has not been reported previously. Our finding suggests that representatives of ANME-2 are potentially able to perform hydrogenotrophic methanogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene of large hydrogenase subunit is a part of the cluster, which codes for uptake hydrogenase small subunit precursor (MCL7474639), four hydrogenase assembly proteins HypDEFC (MCL7474633-36) and hydrogenase maturation protease (MCL7474637). Genes for [FeFe] and [NiFe] hydrogenases were identified in ANME-1 and Methanoperedenaceae [ 23 , 57 , 63 , 64 ], but as far as we know, the presence of hydrogenases in the genomes of ANME-2 has not been reported previously. Our finding suggests that representatives of ANME-2 are potentially able to perform hydrogenotrophic methanogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…This sulfate-reducing bacterium can be cultivated without ANME-1 using hydrogen as an electron donor [ 22 ]. Another thermophilic sulfate-reducing partner of ANME-1 at 70 °C is Candidatus Thermodesulfobacterium torris belonging to the class Thermodesulfobacteria [ 23 ]. Apart from “ Desulfobacterota” , other bacterial groups that have been found to be significantly correlated with ANME are Betaproteobacteria and Verrucomicrobia , but the factors that determine interactions between these bacteria and archaea are not clear [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In searching for thermophilic ANME-1 lineages, we found that cluster VIII, consisting of mcrA genes from ANME-1 enrichments in surficial sediments at 50°C [13], also included Guaymas subsurface mcrA genes from site U1551B. However, we observed no overlap of Guaymas subsurface mcrA genes with mcrA genes from thermophilic methane-oxidizing ANME-1 enrichment cultures that are active at 70°C [15, 17].…”
Section: Resultsmentioning
confidence: 99%
“…Sulfate-dependent anaerobic methane-oxidizing archaea (predominantly ANME-1 and ANME-2) are widespread in surficial sediments of Guaymas Basin (Teske et al, 2002, Biddle et al, 2012, Dowell et al, 2016, McKay et al, 2016). Thermophilic ANME-1 lineages were enriched from hydrothermal sediments of Guaymas Basin at temperatures ranging from 50 to 70°C (Holler et al 2011, Wegener et al 2015, Benito-Merino et al 2022), and at 70°C from Pescadero Basin in the southern Gulf of California (Speth et al 2022, Laso-Pérez et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, in seep sediments, methane could be consumed through the process of anaerobic oxidation of methane (AOM). This process removes roughly 90% of the methane produced globally in marine sediments, acting as an efficient methane filter 3,4 .…”
Section: Background and Summarymentioning
confidence: 99%